Political implications of economic inequality: A literature survey - Laura-Kristin Baric; Niels Geiger (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2019)
This survey documents the different arguments discussed in the academic literature on whether and how economic inequality and the emergence and stability of democratic political systems are connected. While early research in this domain has often focused on new and emerging democracies, this paper also provides an overview of the more recent literature in economics and neighboring fields that discusses democratization as well as established democracies' stability and other institutional traits. In doing so, the survey contains a critical review of both theoretical and empirical contributions on the topic. The different arguments are systematically evaluated and their core hypotheses are distilled in order to document the main lines of argumentation prevalent in the literature. Together with a summary of the theoretical arguments, the main findings of related empirical research are also documented and shortly discussed. Whereas taken together, research so far generally does not suggest any conclusive results concerning economic inequality and the emergence of democracies, the survey indicates that the stability and institutional quality of established democracies can be negatively affected by economic inequality, and it outlines the conditions for this to occur. However, additional research especially on some of the more tentative hypotheses is required to allow for a more profound understanding of the different channels and relationships. Therefore, points of departure for further research, e. g. on how to operationalize specific theoretical constructs of interest and thereby on how to get a better understanding of the relations, are also suggested.
urn:nbn:de:bsz:100-opus-16972
Keywords: D63; D72; 330; economic inequality; institutions; democracy; political stability